Visible-light-absorbing C-N cross-coupling for the synthesis of hydrazones involving C(sp2)-H/C(sp3)-H functionalization - Kushwaha A.K.; Maury S.K.; Kamal A.; Singh H.K.; Pandey S.; Singh S. (My University, 2025)
An efficient C-N cross-coupling approach for the synthesis of hydrazones was developed through C(sp2)-H and C(sp3)-H functionalization of indole and methylarene under visible light irradiation using photocatalyst eosin Y, ethanol:water as a green solvent and atmospheric air as an oxidant. With the aid of eosin Y, the C-H bonds of indole and methylarenes were activated followed by coupling with arylhydrazines. The procedure was applied to a wide variety of substrates with good functional group compatibility, offering a creative way to make hydrazones from inexpensive and easily accessible raw materials. The absence of metals, low cost, environmental friendliness, green solvent, non-toxicity, ease of handling, and utilization of renewable energy sources like visible light are some of this method's primary advantages. © 2023 The Royal Society of Chemistry.